Pengaruh Model Role Playing Terhadap Hasil Belajar Siswa - Aisyah, Ramayni; Muliati, Indah (An-Nuha, 2023)
This study aims to see the effect of the Role Playing model on the Learning Outcomes of Class XI PAI at SMAN 1 Ulakan Tapakis. The sampling technique in this study used purposive sampling. Methods of data collection in this study using questionnaires and tests of student learning outcomes. The results of the validity of the questions in this study showed that 16 questions were valid out of the 25 questions tested. The reliability of the questions using Cronbach alpha obtained a value of 0.779 <0.789 which means the questions have high reliability. Prior to testing the hypothesis, the normality test, homogeneity test, linearity test, and simple linear regression test were carried out. In the normality test for the experimental class, a sig value of 0.151> 0.05 was obtained and in the control class, a sig value of 0.200> 0.05 was obtained. In the homogeneity test, the sig value Fcount<Ftable was obtained, namely 2.015<4.012. In the linearity test, the sig value was 0.486 > 0.05. Meanwhile, in the simple linear regression test, a sig value of 0.018 <0.05 was obtained. The data in this research were analyzed using the independent sample T-test. The research results show: 1) the implementation of the Role Playing learning model is at 79.01% in the highest category; 2) The learning outcomes of experimental class students are in the very high category, it is known that in the 98-103 interval it has the highest frequency with 17 students or 51.52%. 3) The results of testing the hypothesis obtained Tcount = 6,955> Ttable = 4,039.